2005
DOI: 10.1007/bf02344728
|View full text |Cite
|
Sign up to set email alerts
|

Using recurrent artificial neural network model to estimate voluntary elbow torque in dynamic situations

Abstract: Muscle modelling is an important component of body segmental motion analysis. Although many studies had focused on static conditions, the relationship between electromyographic (EMG) signals and joint torque under voluntary dynamic situations has not been well investigated. The aim of this study was to investigate the performance of a recurrent artificial neural network (RANN) under voluntary dynamic situations for torque estimation of the elbow complex. EMG signals together with kinematic data, which included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 22 publications
0
53
0
Order By: Relevance
“…Among the many variations of the back propagation training methods, back propagation with the LevenbergMarquart (LM) algorithm was selected for producing the fastest convergences for medium-sized neural networks up to hundreds of neurons [32]. Its formula can be expressed as follows:…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Among the many variations of the back propagation training methods, back propagation with the LevenbergMarquart (LM) algorithm was selected for producing the fastest convergences for medium-sized neural networks up to hundreds of neurons [32]. Its formula can be expressed as follows:…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…They concluded that ANN model performed reasonably well in estimating joint torque after back-propagation learning, despite of their results not aiming at predicting joint torques but those relationships. Very similar to the study of Luh et al (1999) on elbow joint torque estimating from EMG and kinematic data, Song and Tong (2005) used recurrent artificial neural network (RANN) model to estimate voluntary elbow torque in dynamic situations. EMG signals combined together with kinematic data (angle and angular velocity) were used as the inputs to estimate the expected torque during movement.…”
Section: Discussionmentioning
confidence: 99%
“…Predicted muscle activities were then used by a Hill-type model in order to estimate muscle forces and elbow joint torque. (Song and Tong, 2005) also investigated a recurrent artificial neural network (RANN) for elbow torque estimation using EMG data, elbow joint angle and angular velocity. (Hahn, 2007) used a three-layer FFANN to predict isokinetic knee extensor and flexor torque based on age, gender, height, body mass, EMG signals, joint position and joint velocity.…”
mentioning
confidence: 99%